Distributed Multimedia System for Distance Education - Sharma, Gajendra; Shakya, Subarna; Thapa, Lal Bahadur R. (Journal of the Institute of Engineering, 2019)
A distributed multimedia system (DMS) come to play as a backbone of 21th century to provide sophisticated technology to realize such a modern distance education/learning. In this paper, we describe distributed multimedia system for distance education that could be implemented at Kathmandu University and how this system interacts with other University i.e. Tribhuvan University. Proposed framework brings an abstraction and its infrastructure for multimedia materials storage, management, real time review of this multimedia on demand and a shared whiteboard on web browser to distance learner. For the design of the proposed system, it is necessary to consider different requirement and management of Quality of Service (QoS). This system is made available to only registered student/users through various networks i.e. Local Area Network (LAN)/Internet using university’s own VPN user ID and Password. In addition, proposed system provides abstraction in which distance learner or student access lecturer presentation/notes on web browser and can review multimedia lecture’s notes, presentation on demand. Student or people could have different reasons for attending distance education/learning such as constraints of time, distance, and finance etc. So, distance education system should reduce the distance gap between a student/participants and lecturer. This is done by quick response interaction between lecturer and student throughout the system. The main objective of this paper is to provide distance education platform while guarantying secure communication and user on demand multimedia access with the sophisticated QoS.